Trehalose Synthesis by Sequential Reactions of Recombinant Maltooligosyltrehalose Synthase and Maltooligosyltrehalose Trehalohydrolase from Brevibacterium helvolum - Kim, Yong Hwan (American Society for Microbiology, 2000)
A DNA fragment encoding two enzymes leading to trehalose biosynthesis, maltooligosyltrehalose synthase (BvMTS) and maltooligosyltrehalose trehalohydrolase (BvMTH), was cloned from the nonpathogenic bacterium Brevibacterium helvolum. The open reading frames for the two proteins are 2,331 and 1,770 bp long, respectively, and overlap by four nucleotides. Recombinant BvMTS, BvMTH, and fusion gene BvMTSH, constructed by insertion of an adenylate in the overlapping region, were expressed in Escherichia coli. Purified BvMTS protein catalyzed conversion of maltopentaose to maltotriosyltrehalose, which was further hydrolyzed by BvMTH protein to produce trehalose and maltotriose. The enzymes shortened maltooligosaccharides by two glucose units per cycle of sequential reactions and released trehalose. Maltotriose and maltose were not catalyzed further and thus remained in the reaction mixtures depending on whether the substrates had an odd or even number of glucose units. The bifunctional in-frame fusion enzyme, BvMTSH, catalyzed the sequential reactions more efficiently than an equimolar mixture of the two individual enzymes did, presumably due to a proximity effect on the catalytic sites of the enzymes. The recombinant enzymes produced trehalose from soluble starch, an abundant natural source for trehalose production. Addition of α-amylase to the enzyme reaction mixture dramatically increased trehalose production by partial hydrolysis of the starch to provide more reducing ends accessible to the BvMTS catalytic sites.